2018
DOI: 10.1093/mnras/sty1426
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ELT distortions and instabilities on future astrometric observations

Abstract: The paper discusses an assessment study about the impact of the distortions on the astrometric observations with the Extremely Large Telescope originated from the optics positioning errors and telescope instabilities. Optical simulations combined with Monte Carlo approach reproducing typical inferred opto-mechanical and dynamical instabilities, show RMS distortions between ∼ 0.1-5 mas over 1 arcmin field of view. Over minutes timescales the plate scale variations from ELT-M2 caused by wind disturbances and gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…We demonstrated that chip array instabilities can seriously degrade high-precision astrometry if left uncorrected. The MICADO near-infrared camera (Davies et al 2010) for the ELT aims at a single-epoch accuracy of ≤50 µas over an FOV of 53 (Rodeghiero et al 2018;Pott et al 2018). The detector of MICADO is a 3 × 3 array, and if the reference field is expanded over the full FoV, the RCM effect can fragment it into 3 × 3 segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that chip array instabilities can seriously degrade high-precision astrometry if left uncorrected. The MICADO near-infrared camera (Davies et al 2010) for the ELT aims at a single-epoch accuracy of ≤50 µas over an FOV of 53 (Rodeghiero et al 2018;Pott et al 2018). The detector of MICADO is a 3 × 3 array, and if the reference field is expanded over the full FoV, the RCM effect can fragment it into 3 × 3 segments.…”
Section: Resultsmentioning
confidence: 99%
“…The further accuracy improvement beyond 0.1 mas, needed for the detection of Neptune-and lower-mass companions to ultracool dwarfs, is restrained by fundamental limits on the precision of photocenter determination, the atmospheric image motion caused by turbulence in the upper atmospheric layers, and by systematic errors of instrumental origin. It is expected that in the near future the achievable astrometric accuracy will be improved to 0.01-0.05 mas on 30 m class telescopes such as the European Extremely Large Telescope (ELT), primarily due to the use of adaptive optics, better signal-to-noise ratio in the stellar images, and general performance improvements of the cameras (Davies et al 2010;Rodeghiero et al 2018;Pott et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since we only seek to estimate three parameters, averaging over more than three stars is quickly giving higher accuracy. We showed this to be an efficient strategy for stellar clusters in our Galaxy (3) . Extragalactic targets will require selfcalibration between epochs using the fact that the global stretch or rotation of the object is negligible.…”
Section: Sky Calibrationmentioning
confidence: 87%
“…For the ELT, the plate scale stability during observations is expected as 10 -4 , so 2mas over the 20arcsec scale length. Thus for the ELT, distortion drift errors σ plate.scale is 20times larger than σ 3rd.order (3) . The drift of larger than third order distortion terms of the opto-mechanics are negligible in the here discussed context.…”
Section: Distortion Drifts Start To Contribute At Spatial Scales 002mentioning
confidence: 88%
“…This constraint is typically fulfilled for galactic targets and some extragalactic targets nearby (see discussion in Ref. 13) and is well known from previous relative astrometric mission, both space-and ground-based. In particular, large ground-based astrometry relies on low-order astrometric (plate-scale) calibration via reference stars since atmospheric refraction and telescope alignment are never perfectly stable at the required precision levels.…”
Section: Introductionmentioning
confidence: 91%